Multidrug-resistant bacteria and disease progression in patients with end-stage liver disease and after liver transplantation - Friedrich, Kilian; Schamoni, Shigehiko; Wenz, Theresa; Pfeiffenberger, Jan; Rupp, Christian; Gotthardt, Daniel; Houben, Philipp; Haken, Rebecca von; Heininger, Alexandra; Brenner, Thorsten; Mehrabi, Arianeb; Weiss, Karl Heinz; et al. (Journal of gastrointestinal and liver diseases, 2019)
Background: Multidrug-resistant (MDR) pathogens represent an emerging challenge in end-stage liver disease and in liver transplant recipients. - Methods: We evaluated the impact of MDR bacteria upon clinical outcomes in patients with end-stage liver disease (n = 777) at the time of enrollment on the liver transplant (LTx) waiting list, after first LTx (n = 645), and after second LTx (n = 128). - Results: Colonization/infection with MDR bacteria was present in 72/777 patients on the waiting list, in 98/645 patients at first LTx, and in 46/128 patients at second LTx. While on the LTx waiting list, the time until first hydropic decompensation (p = 0.021), hepatic encephalopathy (p < 0.001) and hepatorenal syndrome (p < 0.001) was reduced in the presence of MDR bacteria, which remained an independent risk factor of poor survival in multivariate analysis (p < 0.001). Following first and second liver transplant, MDR bacteria were associated with an increased risk of infection-related deaths (first LTx: p < 0.001; second LTx: p = 0.037) and reduced actuarial survival (first LTx: p < 0.001; second LTx: p = 0.046). - Conclusions: We showed that MDR pathogens are associated with poor outcomes before, after first and after recurrent LTx.
Gesehen am 04.11.2019